Carbon footprint generated by individual port websites. The missing idea in the concept of green ports - Małgorzata Bielenia; Anna Podolska (Frontiers in Environmental Science, 2023)
One of the objectives of European Union policy, as well as the assumptions of cooperation as part of United Nations, is to ensure sustainable development. The gradual decarbonisation of the economy is a significant element in this case. This is particularly important in transport, including maritime transport. That is why the concept of Green Ports is so important. It contains various infrastructure solutions that maximize the benefits of maritime transport while minimizing environmental damage. However, the term Green Ports is defined in the literature it is difficult to have a clear definition, a formula that defines the term and there is still a place for scientific research in this area. The purpose of the research is to analyze the assumptions of the Green Ports concept in economic terms, but also in legal terms. The authors want to focus on Internet infrastructure as a link in reducing the carbon footprint in maritime transport. For this purpose, they studied the carbon footprint generated by the websites of selected seaports (seaports considered by the Transport and Environment report (https://www.transportenvironment.org/discover/port-carbon-emissions-ranking/) the most polluting European ports and ports considered by the Leading Maritime Cities 2022 report to be the most technologically advanced (DNV, Menon Economics, 2022 https://www.dnv.com/maritime/publications/leading-maritime-cities-of-the-world-2022.html). Both at the United Nations and at the level of organizations of a regional nature (such as the European Union), the use of new technologies is closely linked to economic development or social progress. For example, access to the Internet has been recognized by the United Nations General Assembly as a human right. This is because it has been recognized that the Internet provides an opportunity to realize other rights, such as freedom of expression, the right to information, and education. However, there are also risks associated with the use of new technologies, if only in terms of the right to privacy, intellectual property, security or a clean environment. According to the authors, far less attention is paid to the risks than to the benefits. That’s why it’s worth building awareness to prevent harm rather than repair it. An important aspect of the research is to show that websites consume large amounts of energy. In addition, they have a negative impact on the environment, influencing the production of a significant amount of carbon dioxide. The main finding from the empirical part is that there is a certain relationship between the generation of CO2 by the ports and the “cleanliness” of their websites.